IRMPD Spectra of Protonated Hydroxybenzaldehydes: Evidence of Torsional Barriers in Carboxonium Ions. Issue 8 (11th March 2020) - Chiavarino, Barbara; Dopfer, Otto; Crestoni, Maria Elisa; Corinti, Davide; Maître, Philippe; Fornarini, Simonetta
Abstract: Protonation at the formyl oxygen atom of benzaldehydes leading to the formation of carboxonium ions yields two distinct isomers, depending on the relative orientation of the proton either cis or trans with respect to the hydrogen atom on the adjacent carbon. In this context, the IR multiple photon dissociation (IRMPD) spectra of protonated ortho, meta, and para ‐hydroxybenzaldehydes (OH−BZH + ), delivered into the gas phase by electrospray ionization of hydro‐alcoholic solutions, are reported in the 3200–3700 cm −1 spectral range. This range is characteristic of O−H stretching modes and thus able to differentiate cis and tran s carboxonium isomers. Comparison between IRMPD spectra and DFT calculations at the B3LYP/6‐311++G(2df2p) level suggests that for both p‐ OH−BZH + and m‐ OH−BZH + only cis conformers are present in the ion population analyzed. For o‐ OH−BZH +, IRMPD spectroscopy points to a mixture comprising one tran s and more than one cis conformers. The energy barrier for cis–trans isomerization calculated for each OH−BZH + isomer is a measure of the degree of π‐electron delocalization. Furthermore, IRMPD spectra of p‐ OH−BZH +, m‐ OH−BZH + and protonated phenol (this last used as reference) were recorded also in the fingerprint range. Both the observed C−O and O−H stretching vibrations appear to be a measure of π‐electron delocalization in the ions. Abstract : Showing strengths : O−H stretching frequencies of protonated p‐ hydroxybenzaldehyde and m‐ hydroxybenzaldehyde prove to be a sensitive indicator of the strength of conjugative interaction between substituents through the π‐electron system.